منهج أهل البيت (ع) في تفسير القرآن الكريم: قراءة في الروايات التفسيرية - زاده حسين مناحي; رشيد سامان سلمان (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research aims to study the role of the Ahl al-Bayt (AS) in interpreting the Quran by analyzing the interpretive narrations attributed to them, in order to understand their methodology in interpreting the Quranic text and derive its scientific and practical dimensions. The research relies on studying Shiite sources of interpretive narrations, such as books of Hadith and Tafsir, and analyzing the types of these narrations (direct, indicative, and applicative), with a focus on critiquing them according to precise scientific criteria. The research also examines the interpretive applications of the Ahl al-Bayt (AS) in the fields of creed, rulings, stories, and ethics, aiming to highlight their role in clarifying the meanings of the Quran and guiding its understanding. The research shows that the narrations of the Ahl al-Bayt (AS) form an important foundation for the Shiite interpretive school and significantly influence jurisprudence and creed. Additionally, the research discusses the challenges of relying on these narrations, such as issues related to their chains of transmission and content, and provides a critical perspective to evaluate the interpretive methodology of the Ahl al-Bayt (AS). Through this research, it becomes clear that the narrations of the Ahl al-Bayt (AS) serve as a bridge between the Quranic text and a deeper understanding of its meanings, reinforcing their position as a scientific and religious authority.